Agricultural Development in Asia and Africa Essays in Honor of Keijiro Otsuka - Estudillo, Jonna P.; Kijima, Yoko.; Sonobe, Tetsushi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This Open Access book explores the multifaceted nature of agricultural and rural development in Asia and examines the extent to which the Asian experience is being replicated in contemporary Africa. This volume compiles the works of top scholars who provided analyses and evidences from household-level surveys collected for many years in several parts of Asia and Africa. The most important finding presented in this book is that African agricultural development has evolved following the pathways of Asian agricultural development. The common pathways are borrowed technology from abroad and adaptive research in rice farming; secured property rights on natural resources; adoption of ICTs; investments in human capital, including training; and launching of the high-value agriculture. In both continents, agricultural development started in the crop sector, which had a strong tendency to induce the dynamic development of other sectors in rural areas.
You$1 (Bve Come a Long Way Since -- Introduction: Agricultural Development in Asia and Africa -- Are the Lessons from the Green Revolution Relevant for Agricultural Growth and Food Security in the Twenty-first Century?.-The Central Luzon Loop Survey: Rice Farming in the Philippines from 1966 to 2021 -- Diffusion of Submergence-tolerant Rice in South Asia -- Toward a Green Revolution in Sub-Saharan Africa: Farm Mechanization in the Mwea Irrigation Scheme -- How Can We Achieve Green Revolution in Sub-Saharan Africa? The Case of Tanzania -- A UFO? Assessment of System of Rice Intensification from the Agricultural Economics Perspective -- RePEAT: Looking Back on 20 Years of Achievements -- Fifty Years of Research on Land Tenure Policies and Land Markets: What are the Major Lessons? -- Property Rights and Natural Resource Management in Developing Countries Sustaining Natural Resources in African Agriculture: What Have We Learned in the Past Two Decades? -- Integrated Farming Management Practices in Sub-Saharan Africa: Toward a Sustainable African Green Revolution -- Impacts of Transboundary Crop Diseases on Sustainable Crop Production: The Case of Maize Lethal Necrosis (MLN) in Africa -- Sustainable Green Growth in Agriculture:The Role of Regional Cooperation -- Facilitating Inclusive Use of ICTs in Rural China EdTech for Equity in China: Can Technology Improve Teaching for Millions of Rural Students?.-Mobile Revolution and Rural Development Tomoya Matsumoto and Ggombe Kasim Munyegera Transformation of Rice-Growing Villages in the Philippines -- Structural Transformation and Development Experience from Asian Countries -- Mechanization and the Intersectoral Migration of Agricultural Labor -- Blue Revolution in Asia: The Rise of the Shrimp Sector in Vietnam and the Challenges of Disease Control -- IntegratingAgricultural and Industrial Development -- Cluster-based Agricultural Development: A Comparison Between China and Africa -- Solar Power to Transform Food Systems and Rural -- Livelihoods: Evidence from a Solar-Powered Cold Storage Intervention in Nigeria -- Measuring Women$1 (Bs Empowerment and Gender Equality through the Lens of Induced Innovation -- Competition, Antitrust, and Agricultural Development in Asia -- Summary and Conclusions.s
Keywords: Agriculture -- Economic aspects; Development economics; Economic development; Agriculture; Agricultural Economics; Development Economics; Development Studies; Agriculture